Makna dan Fungsi Mantra Kejawen Aji Seduluran bagi Kehidupan Kolektif Masyarakat Kecamatan Pager Rejo Kabupaten Mojokerto Jawa Timur - Shinta Emilia Ervita (Aksara: Jurnal Bahasa dan Sastra, 2018)
This study talks about of Javanese spells which is still believed by the people of Pager Rejo Village, District of Mojokerto, East Java. This study aims to reveal the meaning and the function of the spell named Aji Seduluran which is still believed by those people. This study uses qualitative research method with two theories, the theory of Alan Dundes is used as the reference for the function of the spell, and the theory of Roland Barthes is used as the reference for the meaning of the spell. Some aspects that will be studied are used to reveal the function and the meaning of Aji Seduluranspell based on the tradition of the people of Pager Rejo Village. The data that have been collected are the spell and the pronunciation to the related people, and some explanations of the people about the origin and the function of the spell for the related people. The data source used in this study is the spell which is believed by the people of the Pager Rejo Village. The result of this study is revealing the meaning and the function of the spell itself.Keywords: Javanese Spells, Oral Poetry, Javanese SocietyDOI: http://dx.doi.org/10.23960/aksara/v19i2.pp89-97